2019
DOI: 10.2147/ott.s199615
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of candidate biomarkers correlated with the diagnosis and prognosis of cervical cancer via integrated bioinformatics analysis</p>

Abstract: Background: Cervical carcinoma is one of the most common malignant gynecological tumors and is associated with high rates of morbidity and mortality. Early diagnosis and early treatment can reduce the mortality rate of cervical cancer. However, there is still no specific biomarkers for the diagnosis and detection of cervical cancer prognosis. Therefore, it is greatly urgent in searching biomarkers correlated with the diagnosis and prognosis of cervical cancer. Results: The mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…A total of three datasets (GSE63514, GSE9750 and GSE7410) were selected for further investigation. Among these, GSE63514 and GSE9750 have been analyzed together (26,27). Other studies have also mined the GSE63514 (28) and GSE9750 (29) datasets; only the GSE7410 dataset had not yet been thoroughly examined previously, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…A total of three datasets (GSE63514, GSE9750 and GSE7410) were selected for further investigation. Among these, GSE63514 and GSE9750 have been analyzed together (26,27). Other studies have also mined the GSE63514 (28) and GSE9750 (29) datasets; only the GSE7410 dataset had not yet been thoroughly examined previously, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using a comprehensive bioinformatics analysis, Xia et al [7] demonstrated that ANLN was dramatically up-regulated in CC tissues, where it predicts poor prognosis. Dai et al [8] identified that the lower expression of KLF4 and ESR1 is closely related to the poor prognosis of patients with CC. Therefore, analyzing the gene expression profiles and the interaction of differentially expressed genes (DEGs) network of CC tissues is vital for understanding the molecular mechanisms of the causes and pathogenesis of CC and the identification of new prognostic biomarkers that may be exploited therapeutically.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA hsa-miR-107, as the hub in this network, was reported to be overexpressed in gastric carcinoma and promote tumor growth and survival [39]. Many researchers have shown that PPP1R3C, PPKAR2B and AKT3 may play important roles in cervical cancer [40], cardiovascular events [41] and prostate cancer [42]. In addition, lncRNAs TUG1, an important regulator of cancers, could facilitate proliferation and suppressed apoptosis by regulating miR-132-3p in osteosarcoma cells [43].…”
Section: Discussionmentioning
confidence: 99%